2014
DOI: 10.1208/s12248-014-9677-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacology and Toxicology of Pharmaceuticals in the Environment: Diphenhydramine Protection of Diazinon Toxicity in Danio rerio but Not Daphnia magna

Abstract: Abstract. Pharmaceuticals and other contaminants of emerging concern present unique challenges to environmental risk assessment and management. Fortunately, mammalian pharmacology and toxicology safety data are more readily available for pharmaceuticals than other environmental contaminants. Identifying approaches to read-across such pharmaceutical safety information to non-target species represents a major research need to assess environmental hazards. Here, we tested a biological readacross hypothesis from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 59 publications
4
32
2
Order By: Relevance
“…Such behavior observations were consistent with our initial age-specific and time of day studies reported above. However, unlike our previous observations of increased DZN acute mortality with increasing zebrafish age (Kristofco et al, 2015), age-specific differences for DZN behavioral toxicity was not consistently observed in the present study (Fig. 2), though several treatment levels significantly decreased activity of 7 dpf and 10 dpf zebrafish compared to 4 dpf organisms.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Such behavior observations were consistent with our initial age-specific and time of day studies reported above. However, unlike our previous observations of increased DZN acute mortality with increasing zebrafish age (Kristofco et al, 2015), age-specific differences for DZN behavioral toxicity was not consistently observed in the present study (Fig. 2), though several treatment levels significantly decreased activity of 7 dpf and 10 dpf zebrafish compared to 4 dpf organisms.…”
Section: Resultscontrasting
confidence: 99%
“…Tropical 5D wild type zebrafish ( Danio rerio ) were maintained under standard culture conditions at Baylor University as previously described (Kristofco et al, 2015; Usenko et al, 2011). Briefly, zebrafish were raised ≤5–6 adult fish per 1.5 L tank in a filtered (Compact system, Lifeguard Aquatics, Cerritos, CA, USA) recirculating z-mod system (Marine Biotech Systems, Beverly, MA, USA) maintained at 28 °C on a 16 h light/8 h dark photoperiod.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations